PENGARUH INTENSITAS ASET TETAP, TINGKAT HUTANG, DAN PROFITABILITAS TERHADAP TARIF PAJAK EFEKTIF - Irda Dayanti; Nana Umdiana; Lulu Nailufaroh (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This Study arms to discuss the factors that affect the effective tax rate. There are several factors used include Fixed Asset Intensity, Leverage and Profitability. The purpose of this study is to discuss the influence of Fixed Asset Intensity, Leverage and Profitability on Effective Tax Rate at Manufacturing Companies Sub. Sector Food and Beverages that listed in Indonesia Stock Exchange Periods of 2016-2019. This research was conducted using quantitative methods with an associative approach. The type of data used in this study according to the time of collection is time series. The population used as the object of observation was 19 manufacturing companies food and beverages sub-sector listed in Indonesia Stock Exchange in the periods of 2016-2019. Determination of the research samples using purposive sampling method and obtained a sample of 13 manufacturing companies based on certain criteria by observation for 4 years. The analytical tool used in this study is multiple linear regression analysis by The IBM SPSS Statistic Version 25. The results showed than fixed asset intensity does not significant effect on the effective tax rate, leverage does not significant effect on the effective tax rate, and profitability have a significant effect on the effective tax rate. In this study, there are still many limitations and shortcomin namely the influence of the independent variable on the dependent variable can only explain by 14.2%.